Edukasi Pencegahan Penularan Tuberkulosis di Desa Sibedi, Kecamatan Marawola, Kabupaten Sigi - Febrianti, Nur; Rosita, Rosita; Iriani, indri (Borneo Community Health Service Journal, 2025)
Tuberculosis sufferers are increasing, data in Sigi Regency is 0.40% who suffer from Tuberculosis so that to deal with this increase, it is necessary to provide education to the community to prevent the transmission of Tuberculosis. The purpose of carrying out community service for efforts to prevent Tuberculosis through providing education in Sibedi Village, Marawola District, Sigi Regency, Central Sulawesi Province. Participants who took part in this activity were 20 people. The form of implementation of this community service activity is in the form of providing education about efforts to prevent Tuberculosis. the media used are power points and leaflets. This activity is carried out once. Results: the service was carried out on Thursday, July 27, 2023 at 03.00-05.00 PM. When the activity began, the community was very enthusiastic to listen to the materials we presented. During the material delivery session, it turned out that many residents did not know about Tuberculosis. This is reflected in the many questions asked regarding the disease. Of the 20 residents who attended, 4 people were found to have had signs and symptoms of Tuberculosis. conclusion: the community service was carried out smoothly, the community response was very good and it is hoped that this community service activity can be carried out routinely.